STUDENT-GENERATED COMMUNICATION ACTIVITIES IN AN ENGLISH FOR SPECIFIC PURPOSES COURSE - Wierciak, Anna (Neofilolog, 2018)
Designing English for Specific Purposes (ESP) courses is a challenging task. The teacher often has to cope with time constraints, shortage of resources as well as his or her insufficient knowledge of a given field of study. Students enrolled in a course are often consulted about the source of materials for instruction. The process of developing ESP tasks can be made easier and less time-consuming by means of employing student-generated communication activities which draw on learner-based approaches to teaching. The paper contains a collection of student-generated tasks that can be successfully used at the preparatory, follow-up or main stage of an ESP class. In the author’s teaching context on numerous occasions they have triggered lively exchanges between students: discussion, brainstorming, or negotiation. Student-generated activities naturally develop collaboration and autonomy, which are essential in the workplace environment. Just like communication skills, they have to be taught explicitly due to the fact that in the area of soft skills there exist considerable differences at the personal and culture-specific level. Finally, since students’ specialist knowledge is usually much better than that of the teacher, student-generated activities tend to be to the point, up-to date, or more precise with respect to the course objectives.